Anchorage in steel fiber reinforced concrete – concept, experimental evidence and design recommendations for concrete cone and concrete edge breakout failure modes. (15th February 2019) - Tóth, Máté; Bokor, Boglárka; Sharma, Akanshu
Highlights: Behavior of anchorages in SFRC is experimentally investigated. Concrete breakout capacity increases due to the presence of fibers. Anchors can sustain larger displacements in SFRC. Design recommendations are given for the use of anchorages in SFRC. Proposal for anchor installation parameters in SFRC. Abstract: A large number of studies confirm the beneficial effects of the steel fiber reinforcement in concrete structures. The addition of steel fibers to the concrete mix leads to better mechanical and physical concrete properties including higher fracture energy, reduced crack widths, higher impact and abrasion resistance, increased durability. Due to the increasing popularity of using anchorages in steel fiber reinforced concrete (SFRC), it is essential to understand the behavior of anchorages in SFRC and to validate the applicability of the current provisions for the design of anchorages for use in structural concrete. However, there is only little research available on the behavior of anchorages in SFRC. This paper presents the results of experimental investigations on tension and shear loaded steel anchors in normal-strength plain concrete (PC) and in SFRC. The comprehensive test program includes 62 pull-out and shear loading tests on single anchors and on anchor groups. The test results are discussed in detail to emphasize the influence of steel fiber reinforcement on the load-displacement behavior of fastening systems. The results indicate that the fiber content has a positive effect on the load-displacement behavior of the anchorages, in general. A better utilization of fastening systems can be attained due to the more ductile behavior and due to the crack bridging mechanism of the SFRC. Furthermore, in certain applications and parameter combinations the ultimate load in case of concrete failure may be higher in SFRC compared to PC.